Capacity mechanisms and effects on market structure - Christina Elberg; Sebastian Kranz (Institute of Energy Economics at the University of Cologne (EWI), 2014)
Liberalized electricity markets are characterized by fluctuating priceinelastic demand of non-storable electricity, often defined by a substantial market share held by one or few incumbent firms. These characteristics have led to a controversial discussion concerning the need for and the design of capacity mechanisms, which combine some form of capacity payments with price caps in the spot market. The purpose of this study is to understand the effects of capacity mechanisms on the market structure. We consider a model with dominant firms and a competitive fringe and investigate the impact of price caps and capacity payments on investment incentives and market concentration. While lower price caps reduce the potential for the exercise of market power in static models, we find that in the dynamic model with endogenous investments, lower price caps result in an increase in market concentration, the frequency of capacity withholding and the profits of the dominant firms.
Keywords: L11; L51; L94; D47; 330; Electricity Markets; Market Design; Market Structure; Capacity Mechanisms; Competitive Fringe